Assisting and regulating virtual enterprise interoperability through contracts - Eugénio da Costa Oliveira (2005)
Virtual Enterprises are a major trend in enterprise interoperability, configuring cooperative settings in which different parties temporarily share their resources towards a common goal. Virtual Enterprises are created in very dynamic environments, and their temporary nature demands for quick set-up phases. In truly open settings, virtual enterprises may comprise business entities whose previous performance record may not be assessed. Contracts formalizing norms of behavior are needed to allow for verification of cooperative business compliance. Contracts also provide a coarse-grained specification of business processes, enough for verifying observance to promised cooperative efforts. In this paper we relate these issues to the increasingly important dichotomy in multi-agent systems: autonomy and openness vs. regulation. We present our approach, including agent-based services provided inside a regulated environment an electronic institution. We then give particular emphasis to contract formalization through norms, their monitoring and enforcement. Our approach assigns contexts to norms, configuring a structured view that addresses the possibility of creating different agents cooperation agreements inside the overall framework.